Production of transgenic carnation with a heterologous 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase bifunctional enzyme cDNA - Szőke, A.; Kiss, E.; Toldi, O.; Heszky, L. (International Journal of Horticultural Science, 2006)
Transgenic carnations were produced with a modified mammalian bifunctional enzyme cDNA coding 6-phosphofructo-2- kinaseffructose 2,6-bisphosphatase. Relative activity of this enzyme determines the fructose 2,6-bisphosphate (fru 2,6-P2) cytosolic concentration. This metabolite — as a signal molecule — is one of the carbohydrate metabolism regulators. The regenerated Dianthus chinensis and Dianthus caryophyllus shoots were selected on MS basal medium containing 150 mg/1 kanamycin. Transgene integration was proven by PCR analysis with cDNA specific primers followed by Southern hybridization of DNA isolated from selected green shoots, which survived on kanamycin containing medium, so 3 D. chinensis and 20 D. caryophyllus transgenic plants were produced. Transgene expression were examined by RT-PCR. Transformed and control plants were potted in glasshouse to evaluate the effect of modified fru 2,6-P2 on development, growth and carbohydrate metabolism.